An Analysis of the Political Dynamics that Influenced the Process of Adopting the 2016 National Land Laws in Malawi: A Gender Perspective - Thindwa, Priscilla (Department of Political Studies, 2020)
The thesis interrogates how the political dynamics that emerged in the formulation of the 2016 land legislation in Malawi influenced the gendered outcomes. It highlights the complexity of the policymaking process that was shaped by divergent interests and power dynamics of the stakeholders. It argues that although the interests and agenda complicated the process, their discourses were framed and justified their positions within the development and gender equality framework. It highlights the progressive nature of the socio-legal provisions in the legislation by significantly recognising and promoting women’s land rights. It contends that advances in legal institutions are essential; however, for inclusive transformation to be sustainable, changes in social and cultural practices and norms are imperative. This is because Malawian women continue to face exclusion in owning, controlling and accessing land albeit being the major agricultural producers. This is owed to the persistence of patriarchal attitudes in institutions that perpetuate contestation in the public and private spheres of women’s rights to access, own and control over land. Such is persistent particularly within customary laws which remain sites of struggle between traditional leaders’ claims and women’s societal positions. Hence, creating enabling environments for women will allow them to articulate their political voices and agenda and as such influence policy and legal formulation. Through a multi-faceted approach encompassing of legal pluralism, feminist perspectives on gender and development, and the theory of change, the paper discusses the complexity of policymaking that has been shaped by interests and power. For instance, most chiefs contested against their limited powers and the inclusion of women in land administration issues as stipulated in the new Land Laws, while CSOs advocated for the laws to be people-centred, gender-sensitive and responsive to women’s needs. Also, International organisations were interested in ensuring that there is improved land governance framework and its implementation is in line with VGGT. Thus, apparent realities emerge from the analysis of these political dynamics within the adoption of the 2016 Land Laws: the differing stakeholders’ agenda and how they all pressed on advancing their agenda. Nonetheless, gender equality and development discourse was an aspect that was apparent in the debates.